Prevalence and associated factors of schistosomiasis among pregnant women in northern Senegal - Coumba Nar Ndiour; Bruno Senghor; Ousmane Thiam; Souleymane Niang; Amélé Nyedzie Wotodjo; Babacar Thiendella Faye; Ndeye Amy Ndiaye; Omar Sow; Khadime Sylla; Magatte Ndiaye; Oumar Gaye; Babacar Faye; et al. (BMC Infectious Diseases, 2024)
Abstract Background Schistosomiasis remains a public health concern worldwide. It is responsible for more than 240 million cases in 78 countries, 40 million of whom are women of childbearing age. In the Senegal River basin, both Schistosoma haematobium and Schistosoma mansoni are very prevalent in school-age children. However, there is a lack of information on the burden of schistosomiasis in pregnant women, which can cause complications in the pregnancy outcome. This study aimed to determine the prevalence and associated factors of schistosomiasis in pregnant women. Methods We conducted a prospective cross-sectional study of pregnant women attending antenatal clinics at the health center of the Senegalese Sugar Company and at the hospital of Richard Toll between August and December 2021. The urine and stool samples collected were examined using microscopy techniques and quantitative polymerase chain reaction (qPCR) to detect the presence of S. haematobium and S. mansoni. The urines were previously tested using urine reagent strips to detect hematuria and proteinuria. Socio-demographical, clinical, and diagnostically data were recorded by the midwife and the gynaecologist. The data were analyzed using a logistic regression model. Results Among the 298 women examined for the infection by microscopic, 65 (21.81%) were infected with urogenital schistosomiasis, 10 (3.36%) with intestinal schistosomiasis, and 4 (1.34%) were co-infected with both types of schistosomiasis. Out of the 288 samples tested by qPCR, 146 (48.99%) were positive for S. haematobium, 49 (35.51%) for S. mansoni and 22 (15.94%) for both species (co-infection). Pregnant women having microscopic haematuria and proteinuria were significantly more infected (p < 0.05). Conclusion This study has revealed a high prevalence of schistosomiasis in pregnant women in Senegal. The qPCR allowed us to detect more cases compared to the microscopy. There is a need to conduct more studies to understand the real burden of the disease and to set up a surveillance system to prevent pregnancy-related complications.